Basophil Activation Test identifies the patients with Chronic Spontaneous Urticaria suffering the most active disease. Issue 4 (4th October 2016) - Curto‐Barredo, Laia; Yelamos, Jose; Gimeno, Ramon; Mojal, Sergi; Pujol, Ramon M.; Giménez‐Arnau, Ana
Abstract: Introduction: The basophil activation test showing CD63 up regulation could be a specific and sensitive in vitro complementary text to the in vivo autologous serum skin test for the activity assessment of the patients suffering autoimmune chronic spontaneous urticaria. The aim of this study is to define the basophil activation test as a useful tool in clinical practice in order to identify those patients with more active disease. Methods: We screened 139 patients (96 women) diagnosed of chronic spontaneous urticaria using simultaneously autologous serum skin test and basophil activation test and their relationship with disease activity. Results: Positive autologous serum skin test was found in 56.8%; from them, 31.6% were basophil activation test positive. Negative autologous serum skin test result was found in the 43.2% of the sample that showed negative CD63 expression results in all cases, except one. Patients with positive autologous serum skin test and positive CD63 by basophil activation test showed significant higher Urticaria Activity Score of 7 days ( P = 0.004) and of 3 weeks ( P = 0.001) than patients with positive autologous serum skin test and negative CD63 (mean ± standard deviation [SD] 26.57 ± 10.56 versus 18.40 ± 12.05 for the Urticaria Activity Score of 7 days and 56.47 ± 23.78 versus 39.88 ± 25.44 for the Urticaria Activity Score of 3 weeks). Conclusions: The CD63 expression on basophils appears as a reliable in vitro marker, useful in clinical practice in combination with autologous serum skin test to define chronic spontaneous urticaria patients with the highest urticaria activity that impairs a normal life. Abstract : The successfull management of Chronic Spontaneous Urticaria requires an effective identification of the patients for which the disease is more active. The assessment of the CD63 expression using the basophil activation test in routine clinical practice confirm the most severe patients with autoimmune urticaria. The basophil activation test is less invasive than the current tools available to test serum autorreactivity in chronic spontaneous urticaria.